Estilos de liderazgo en los gerentes de agronegocios dedicados a la producción de plátano (MUSA AAB) adscritos a la empresa Agrocaribe - Álvarez Chila, Gema Maridalia (2023)
The plantain (Mussa AAB) has great socioeconomic importance for Ecuador as it is a basic component in the daily diet of the rural population, as well as the food supply of the Ecuadorian population in general, being considered as a support for the economy and food security of the country. country. Given the importance, this work aimed to determine the leadership styles in the managers of the Agribusinesses dedicated to the production of plantain (MUSA AAB) attached to the company AgroCaribe S.A. and its influence on decision making. First, the technical and commercial functions of the AgroCaribe company were identified; Secondly, the agribusinesses dedicated to the production of bananas that are attached to the company AgroCaribe S.A. were characterized. and finally, the relationship between leadership styles and managerial decision-making of agribusinesses dedicated to plantain production was established.